If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 2n + 16 = n + 7 Reorder the terms: -4 + 16 + 2n = n + 7 Combine like terms: -4 + 16 = 12 12 + 2n = n + 7 Reorder the terms: 12 + 2n = 7 + n Solving 12 + 2n = 7 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 12 + 2n + -1n = 7 + n + -1n Combine like terms: 2n + -1n = 1n 12 + 1n = 7 + n + -1n Combine like terms: n + -1n = 0 12 + 1n = 7 + 0 12 + 1n = 7 Add '-12' to each side of the equation. 12 + -12 + 1n = 7 + -12 Combine like terms: 12 + -12 = 0 0 + 1n = 7 + -12 1n = 7 + -12 Combine like terms: 7 + -12 = -5 1n = -5 Divide each side by '1'. n = -5 Simplifying n = -5
| 1x-2(x+10)=12 | | 7x-9=-4x+90 | | 3(x+5)=3x | | 12*n=12*6 | | -(3-2N)+7N=(N+3) | | 18a-22=-4(1-6a) | | N*1=2 | | 50-6x=-46 | | -5b+24=-8b(b-6)+6b | | 2.5g-14=5 | | 9y^2-72y-81=0 | | x^2+2x+1=11 | | 7+4x=24 | | x^2+40x+384=0 | | 4y+7=6y+14 | | 7+3X=-15 | | -(4x-3)=x+6 | | 4x^2+15x-2.5=0 | | -8*4-6= | | 4x-3=x+6 | | -2=-4x-6x | | 4(3r-2)=3(r+7) | | 7+3x=-22 | | 2-6-4= | | (8x-10)+(8x-10)=6x+6x | | a(-10)-8=-24 | | -3(2x-4)+4x=-34 | | w+(w+6)=334 | | (3r^2)-(10r)= | | 5n+5=10 | | 4x+32=88 | | 3x-3=180 |